A hexanucleotide repeat upstream of eotaxin gene promoter is associated with asthma, serum total IgE and plasma eotaxin levels. Issue 6 (12th January 2007) - Batra, Jyotsna; Rajpoot, Reenu; Ahluwalia, Jasmine; Devarapu, Satish K; Sharma, Surendra K; Dinda, Amit K; Ghosh, Balaram
Abstract : Background: Eotaxin (CCL11) is a small protein produced in the lungs of patients with asthma, and is a potent chemoattractant for eosinophils. Aim: To elucidate the role of eotaxin in asthma by an association study of functional and novel eotaxin polymorphisms in case–control and family-based study designs. Methods: Eotaxin +67G/A, –384A/G and –426C/T single-nucleotide polymorphisms and a hexanucleotide ( GAAGGA )n repeat 10.9 kb upstream of the gene were genotyped in a cohort of age, sex and ethnically matched patients with asthma (n = 235) and healthy controls (n = 239), and also in a study population of 230 families with asthma recruited from north/northwest India. Total serum IgE (TsIgE) and plasma eotaxin levels were measured using ELISA. Results: +67G/A polymorphism was found to be significantly associated with asthma in case–control (p = 0.009) and family-based studies (p = 0.006). Its functional role, as it was correlated with plasma eotaxin levels (p = 0.006), was also demonstrated. Further, –384C/T single-nucleotide polymorphism was found to be significantly associated with log10 TsIgE (p = 0.016 in case–control and p = 0.018 in families) and eotaxin levels (p = 0.007). Most interestingly, for the first time, a highly significant association of the newly studied ( GAAGGA )n hexanucleotide repeat with asthma (p = 3×10 −6 ), log10 TsIgE (p = 0.006) and eotaxin levels (p = 0.004) was observed. G_A_C_8 was also identified as an important risk haplotype associated with high TsIgE and plasma eotaxin levels. Conclusions: This study provides further evidence that eotaxin polymorphisms are associated with the development of asthma by regulating eotaxin levels and reinforces towards the scanning of other chemokine genes present at 17q21 locus for their association with asthma and related phenotypes.